2022
DOI: 10.4067/s0718-58392022000300484
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-chemical characterization of Huanglongbing in mandarin (Citrus reticulata) and orange (Citrus sinensis) varieties from Pakistan

Abstract: Huanglongbing (HLB) is one of the world's worst diseases of citrus trees. The research was conducted to characterize positive citrus samples of two local varieties, 'Kinnow' mandarin (Citrus reticulata Blanco) and 'Mosambi' orange (C. sinensis (L.) Osbeck), based on morphological, physical and biochemical characters. Physical and biochemical parameters of greening infected and healthy samples of both the cultivars were significantly different. Citrus fruits were lopsided and half to full green in the HLB infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Khan et al [26] reported a rapid increase in weight of Orange fruit, from 180 days onwards till 220 days after fruit set; followed by a slow increase up to 250 days. Slightly decreasing trend was observed in Orange at fully mature stage, which might be attributed to higher rate of respiration [27]. In Clementine maximum fruit weight was reported at fully mature stage 95.13g which started to reduce as fruit ripen [28].…”
Section: Fruit Weight and Sizementioning
confidence: 91%
See 1 more Smart Citation
“…Khan et al [26] reported a rapid increase in weight of Orange fruit, from 180 days onwards till 220 days after fruit set; followed by a slow increase up to 250 days. Slightly decreasing trend was observed in Orange at fully mature stage, which might be attributed to higher rate of respiration [27]. In Clementine maximum fruit weight was reported at fully mature stage 95.13g which started to reduce as fruit ripen [28].…”
Section: Fruit Weight and Sizementioning
confidence: 91%
“…Most citrus fruits showed constant rise in TSS content till semi ripe condition due to synthesis of sucrose which then are hydrolyzed to simple sugar [42]. TSS increased slowly in Oranges and Clementine as 12.1 °Brix and 10.8 °Brix at fully mature stage after 240 days after fruit set [27,28]. Nearly 75% to 85% of TSS in orange juice is sugars.…”
Section: Total Soluble Solid (Tss)mentioning
confidence: 99%
“…Our database includes five species of Citrus: C. sinensis , C. limon , C. maxima , C. reticulata , and P. trifoliata . C. maxima , C. sinensis , C. limon , and C. reticulata are severely affected by HLB [ 32 35 ], whereas P. trifoliata is often used as a rootstock and shows tolerance to HLB [ 8 ]. Therefore, we chose the five representative citrus species to construct the database.…”
Section: Construction and Contentsmentioning
confidence: 99%
“…The total output, the total value added, and labor income all decreased, resulting in a loss of $3.9 billion. Symptom-based diagnosis is not practical and the popularity of the PCR technique has grown because of its ability to quickly and sensitively detect even trace amounts of pathogen DNA in both infected plant samples and insect vectors (Sajid et al, 2022). PCR utilizes a fluorescent reporter that binds to the amplified product and emits fluorescence to indicate its presence.…”
Section: Introductionmentioning
confidence: 99%